Uji Aktivitas Ekstrak Biji Asam Jawa (Tamarindus indica) terhadap Asam Urat Mencit Putih Jantan (Mus Musculus) Induksi Kalium Oksonat - Asti Pratiwi; Aminah Syarifuddin; Cucu Arum Dwi Cahya; Melinda Sari (Jurnal Indah Sains dan Klinis, 2023)
Background: The Tropical Tamarind Plant has great economic value and benefits for society, from the stems to the leaves it can be used to treat diseases, such as fever, dyspepsia and even gonorrhoea. The chemical components of Tamarind seeds include alkaloids, saponins, flavonoids, glycosides, malic acid, tartrate, pectin, arabinose, xylose, galactose and glucose. Objective: The study was directed to determine the activity of ethanol extract from tamarind seeds in reducing uric acid in mice. Methods: Preparation of dry extract of Tamarind seeds (EKBAJ), phytochemical screening, and testing the activity of reducing uric acid in mice induced by potassium oxonate at various concentrations of EKBAJ. Measure the levels with Easy Touch GCU. Results: EKBAJ can inhibit mouse uric acid synthesis. The higher the concentration of EKBAJ, the greater the effect on reducing uric acid levels. Conclusion: A concentration of 200 mg/kgBW had the greatest effect on reducing uric acid in mice.